Nasal and Laryngeal Rhinosporidiosis in Horses Treated with Electrocautery - Zibordi, Miriam; Belli, Carla Bargi; de Zoppa, André Luis do Valle; Spagnolo, Julio David; da Silva, Luis Claudio Lopes Correia; Baccarin, Raquel Yvonne Arantes (Acta Scientiae Veterinariae, 2020)
Background: Rhinosporidiosis is considered an endemic disease in some countries and can affect several species of animals, among them, also equines. In this specie, although the nasal cavity is the most common site of infection, in some cases, it could also be spotted in the larynx region. The present study had as an objective to describe two cases of rhinosporidiosis in horses, one of them nasal and the other in the laryngeal area. Cases: Horse 1. A 12-year-old male Standardbred was sent to the veterinary hospital for the resection of the formation presented in the mucocutaneous junction of the left nostril. During the physical exam, a red mass of a moderately consistency, with an irregular, verrucous, pedunculated and ulcerated surface was observed, measuring approximately 2 centimeters in diameter. The surgical procedure for the resection of the mass was done through the use of the electrocautery technique, with the animal sedated with a romifidine dose of 0.08 mg/kg, a butorphanol dose of 0.04 mg/kg and a local anesthesia of 2% lidocaine. Eight months after the surgical procedure, the animal returned to the hospital and the presence of three new masses was noted in the same nostril, around the region where the extracted mass used to be found and they resembled the previous lesions. The horse’s owner didn’t authorize a new surgery or a new histopathological exam of the lesions. Horse 2. The other case refers to an asymptomatic 15-year-old male mixed breed. During a routine gastroscopic exam, the presence of several reddish coloration nodular and polypoid formations of irregular surface was observed in the larynx. Only one formation in the dorsal portion of the pharynx was observed. During the macroscopic exam, it was observed heterogeneously formation with a grayish-white color and soft consistency aspect. The surgical procedure for the resection of the mass, also through electrocautery, was performed with the animal, previously sedated with a detomidine dose of 0.01 mg/kg and a butorphanol dose of 0.02 mg/kg through intravenous. The contact plate of the electrocautery was fixed to the left side of the animal’s neck. After the introduction of the endoscope through the nostril and advancing to the pharynx and larynx, lidocaine 2% without a vasoconstrictor was sprayed in the region. The polyps were individually wrapped by the polypectomy loop, passed through the endoscope operational channel and, at this time, the electrocautery was activated. After the treatment, periodical return appointments were made for the next two months. During the fourth appointment, the animal presented, in the endoscopy, a relapse of a few formations which were, again, removed with electrocautery. The histopathological exam in both cases was characterized by the presence of sporangia that was distributed homogeneously across the submucosal blade interspersed with mild to moderate mixed inflammatory infiltration composed predominantly of lymphoplasmic cells, followed by neutrophils and macrophages, as well as some hemorrhage area and the presence of macrophages with hemosiderin. These histopathological findings were consistent with rhinosporidiosis. Discussion: Rhinosporidiosis in horses, although rare, must be considered not only in cases of nasal formations, their most common form, but also in laryngeal cases, while the use of electrocautery is an efficient technique in the removal of the lesions, allowing for a good tissue healing and no postoperative complications. Nevertheless, follow-ups after treatment is always recommended to identify possible relapses.